High-risk population and factors of stroke has changed among middle-aged and elderly Chinese—Evidence from 1989 to 2015 - Zhang, Xue; Dai, Jing; Li, Wei; Yang, Yunjuan (Frontiers in Public Health, 2023)
Objectives: The present study aimed to investigate the trend of stroke prevalence from 1989 to 2015 in China, explore the transition of high-risk population and high-risk factors, of stroke, and provide some evidence to develop more targeted stroke intervention strategies. Methods: We derived the baseline data from China Health and Nutrition Survey (CHNS). Participants responded to the personal questionnaire containing demographic information, behavioral health information, disease history, and physical examination. We utilized chi square test, Shapley value decomposition model, and decision tree classification model to evaluate the changes of high-risk population and high-risk factors of stroke. Results: Across 42,419 middle-aged and elderly residents, the prevalence of stroke was decreasing from 2.78% to 1.86% from 1989 to 2015. Hypertension was the first factor of stroke, while its contribution rate was weakened from 50.95% to 36.39% with the increasing of medicine taking rate. As the second risk factor of stroke, the contribution of age decreased from 19.78% to 11.01% with the improvement of China’s medical level and the increasing of elderly life expectancy. The contribution rate of historical health factors, behavioral factors, and regional factors, such as body mass index (BMI), diabetes, daily sleep duration, and residence to the impact of stroke was increasing. In addition, the first high-risk population of stroke changed from hypertension patients aged 75 years and above to without spouse residents living in Beijing and Liaoning, and the prevalence of stroke altered from 18% to 9.5%. The second risk population of stroke transformed from male hypertensive patients under 75 years old into male hypertensive patients living in urban, and the prevalence rate decreased from 9.8% to 9.1%. The third high-risk group of stroke turned from the elderly aged 75 and above into the female patients with hypertension and diabetes, and the prevalence rate changed from 6.1% to 7.5%. Conclusions: This study demonstrated that the high-risk population and high-risk factors of stroke changed in China and revealed the direction and internal mechanism of transition of stroke. We should renew targeted stroke intervention strategies.